Keberlanjutan Mabrur: Pendampingan Gerakan Sosial Spriritual Kelompok Alumni Haji Aziziyyah Ismalilyyah KBIH ar-Rahmah Tahun 2024 Wonogiri Jawa Timur - Moh. Isom Mudin; Amrullah, Khasib; Farhah; Saifuddin, Ahmad Farid; Arijal, Hasbi (Wisanggeni: Jurnal Pengabdian Masyarakat, 2025)
The concept of mabrūr demands the continuation of piety both socially and spiritually which has not been realized by the Alumni of the Alumni Group of Hajj Aziziyyah Ismailiyyah Hajj KBIH ar-Rahman 2022 Wonogiri East Java, it is necessary to provide intense assistance from academics so that mabrur continues. The problem that will be used as an object is how the form of assistance and its impact on both individuals and social movements. The method used in this PKM is Participatory Action Research (PAR), specifically with a focus Group Discussion (FGD), technically through initial mapping, building relationships with the community, identifying problems, and taking action. This PKM activity has a tremendous impact in maintaining the prosperity of the congregation after their return from the holy land, both in individual and social aspects. They are able to have an impact on social life by being able to give empathy, elevating the dignity of others from backwardness, ignorance, unemployment, and poverty.